Extraction and concentration of ω-3 and ω-6 fatty acids mixture from algal oil of Schizochytrium mangrovei PQ6 by urea complexation method - Thom, Le Thi; Tam, Luu Thi; Ha, Nguyen Cam; Lan Anh, Hoang Thi; Hoai Thu, Ngo Thi; Minh Hien, Hoang Thi; Hong, Dang Diem (Academia Journal of Biology, 2014)
This paper presented the results of optimal condition for extraction and concentration of ω-3 and ω-6 fatty acids mixture from algal oil of Schizochytrium mangrovei PQ6 by urea complexation method. Influences of free fatty acid (FFA) to urea ratio, urea to EtOH ratio and crystallization temperature were investigated. The obtained results showed the maximum amount of total ω-3 and ω-6 fatty acids (99.29% of TFA) and content of DHA and EPA (87.83% of TFA) were obtained at a FFA to urea ratio of 1:4, a urea to EtOH ratio of 1:9 and a crystallization temperature of 4oC. The physico-chemical parameters such as oil colour, acid, peroxide and iodine values of ω-3 and ω-6 fatty acids mixture production in this study meet the requirements for quality of the raw material used to produce foods, functional foods and pharmaceutical products.